2017
DOI: 10.3329/bjmb.v8i2.33278
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Metabolic Syndrome and Benign Prostate Hyperplasia

Abstract: Metabolic syndrome (MetS) is a highly prevalent complex disorder among adults worldwide which includes cardiovascular risk factors such as central obesity, insulin resistance, dyslipidemia and hypertension. MetS or its components are prevalent in patients with benign prostate hyperplasia (BPH), a common urogenital disorder of adult male with increasing age. This cross-sectional study was conducted in the Department of Biochemistry, Dhaka Medical College, Dhaka from July 2014 to June 2015 with a total of 100 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Age, ethnicity, obesity, genetics, sex steroid hormones, modifiable lifestyle variables, and inflammation are known stimulators of morphological volumetric changes in the prostate gland. Age is one factor that might cause changes in the prostate gland 10 . In this study, we found significant results in the age range of 61-70 years and prostate volume of 30ml when comparing obese and non-obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Age, ethnicity, obesity, genetics, sex steroid hormones, modifiable lifestyle variables, and inflammation are known stimulators of morphological volumetric changes in the prostate gland. Age is one factor that might cause changes in the prostate gland 10 . In this study, we found significant results in the age range of 61-70 years and prostate volume of 30ml when comparing obese and non-obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Benign prostate hyperplasia (BPH) is a focal enlargement of the peri-urethral region of the prostate seen in most aging men, which results in symptoms requiring clinical intervention in approximately onethird of men over the age of 60 years. 1 Currently, BPH is the fourth most prevalent disease in men aged >50 years. 2 In 2013, Indonesia has 9.2 million cases of BPH, most of them were suffered by men aged over 60 years.…”
mentioning
confidence: 99%